Conjugated linoleic acid regulates adipocyte fatty acid binding protein expression via peroxisome proliferator-activated receptor α signaling pathway and increases intramuscular fat content - Chen, Jing; You, Ruiguo; Lv, Yao; Liu, Huimin; Yang, Guoqing (Frontiers in Nutrition, 2022)
Intramuscular fat (IMF) is correlated positively with meat tenderness, juiciness and taste that affected sensory meat quality. Conjugated linoleic acid (CLA) has been extensively researched to increase IMF content in animals, however, the regulatory mechanism remains unclear. Adipocyte fatty acid binding protein (A-FABP) gene has been proposed as candidates for IMF accretion. The purpose of this study is to explore the molecular regulatory pathways of CLA on intramuscular fat deposition. Here, our results by cell lines indicated that CLA treatment promoted the expression of A-FABP through activated the transcription factor of peroxisome proliferator-activated receptor α (PPARα). Moreover, in an animal model, we discovered that dietary supplemental with CLA significantly enhanced IMF deposition by up-regulating the mRNA and protein expression of PPARα and A-FABP in the muscle tissues of mice. In addition, our current study also demonstrated that dietary CLA increased mRNA expression of genes and enzymes involved in fatty acid synthesis and lipid metabolism the muscle tissues of mice. These findings suggest that CLA mainly increases the expression of A-FABP through PPARα signaling pathway and regulates the expression of genes and enzymes related to IMF deposition, thus increasing IMF content. These results contribute to better understanding the molecular mechanism of IMF accretion in animals for the improvement of meat quality.